Online Teaching in Social Work Education: Understanding the Challenges. Issue 1 (2nd January 2019) - Davis, Cindy; Greenaway, Ruth; Moore, Matthew; Cooper, Lyle
ABSTRACT: There is a rapidly growing industry of online learning and distance education programs at the Master of Social Work and Bachelor of Social Work levels both within Australia and globally. A number of best practices have emerged from the literature that warrant consideration when delivering social work programs in online learning and distance education modes. Given the significant advancements in technology that are likely to continue into the next decades, social work academic leaders and accrediting bodies must be prepared to address the changing landscape of higher education, including limited financial resources. Social work academics need to become aware and implement best practices in online learning and distance education e-teaching environments to ensure positive student outcomes, student retention, and student engagement to meet the flexibility needs of students in higher education settings. The purpose of this paper is to identify and discuss the challenges and benefits of distance education and online learning for consideration when providing a social work program in these delivery models. IMPLICATIONS Given the significant advancements in technology that are likely to continue into the next decades, social work academic leaders and accrediting bodies must be prepared to address the changing landscape of higher education. Social work academics need to become aware and implement best practices in the distance education and online teaching environment to ensure positive student outcomes, student retention, and student engagement to meet the flexibility needs of students in higher education settings.